Essays in Contemporary Economics A Festschrift in Memory of A. D. Karayiannis - Bitros, George C.; Kyriazis, Nicholas C.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2015)
This book is a collection of original essays grouped into four parts under the headings (3z(BGreece and European integration,(3y z(BIssues in the Methodology of Economics,(3y z(BInstitutions and the Free Market Economy,(3y (Band (3z(BInsights for Today from Ancient Greece.(3y (BThe essays appeal to both researchers in the corresponding fields of knowledge and also to policy makers who are looking for ideas and approaches to confront present day challenges. In particular, given the present state of turmoil in the European Union, the international economy, and democracies in general, most of the essays offer new insights for economic and social policies.s
Preface -- Part I: Greece and European Integration -- Part II: Issues in the Methodology of Economics -- Part III: Institutions and the Free Market Economy -- Part IV: Insights for Today from Ancient Greece -- Part V: Indices -- Author Index -- Subject Index.
Keywords: Economics; Economic policy; Europe -- Economic policy; International economics; Social policy; Economics -- Methodology; Economics/Management Science; Methodology and the History of Economic Thought; International Economics; European Integration; Economic Policy; Social Policy